Auditoria de enfermagem como estratégia para fortalecimento do núcleo de segurança do paciente. - Juliana Vasconcelos da Silva (Revista ft, 2026)
Introduction: Nursing Audit has established itself as an essential tool in evaluating care processes and promoting the quality of care provided to patients. Through systematic analyses, it contributes to the identification of flaws, prevention of adverse events, and strengthening of the safety culture. In this context, the Patient Safety Center (NSP) stands out as a strategic body responsible for coordinating continuous improvement actions, risk management, and encouraging incident reporting. Objective: To analyze the Nursing Audit as a strategy for strengthening the Patient Safety Center, highlighting its contribution to improving the quality of care and consolidating the hospital safety culture. Methods: This is an integrative literature review with a qualitative, descriptive-exploratory approach. The search was conducted in the LILACS, SciELO, and PubMed databases using the descriptors "Nursing Audit", "Patient Safety", and "Health Management", combined with the Boolean operator AND. Full-text articles published in the last ten years in Portuguese, English, and Spanish were included. The analysis was carried out through careful reading and thematic categorization of the findings. Results: The studies demonstrated that the Nursing Audit constitutes a strategic tool for monitoring care indicators, identifying non-conformities, and implementing corrective actions focused on patient safety. The integration between auditing and the NSP favors the improvement of records, increases incident reporting, and strengthens evidence-based practices, in addition to contributing to continuing education and reducing adverse events. Conclusions: It is concluded that the Nursing Audit strengthens the Patient Safety Center by supporting managerial decision-making and promoting systematic evaluation of processes, contributing to continuous improvement and excellence in care.